African Perspectives of Research in Teaching & Learning (APORTAL) Vol 6 (2) (2022) - Wadesango, Newman editor in chief (African Perspectives of Research in Teaching & Learning (APORTAL), 2022)
Refer to the document
APORTAL Completed issue
Keywords: Professional development; Scholarship of teaching; Community of practice; Practitioner; Discussion classes; Affective factors; Support strategy; Academic performance; Open and distance learning; Addicted learners; Drug addiction; Bronfenbrenner’s Ecological Systems Theory; Critical emancipatory research; Township school violence; Access; African literature; Decolonisation; Mindsets; Technology in education; Neuroticism; School leadership; Dilemma; Quality education; Neurotic context; Education systems; Sub-Saharan Africa; Social justice; Capabilities approach; Pedagogy; Modernity; Ubuntugogy; Rural universities; Africanised pedagogy; Accounting classroom; Challenges; COVID-19; Online teaching; Teaching and learning; Internet; Social media; Students; Learning platform; African languages; Curricula; Decolonisation; Higher education; Opera schools; Awareness; Distance learning; Postgraduate students; Open Distance eLearning; Student support service; Continuous professional development; Desktop research; Impediments; Effective; Efficient; Student success; Collaboration; Colleagueship; Special education; Hearing impairment; Collaboration; In-service training; Pedagogy; Cultural historical activity theory; Guidance and counseling; HIV and AIDS; Participatory visual methodology; Sexuality education; Critical theory; Flexible learning; Hybrid classroom; Sense of splace; Universal design for learning; Leadership; Rurality; Traditional leadership; Successful leadership; Career development; Academic achievement; Curricula; Distance education; Open learning; Ubuntu (Philosophy); Employees -- Training of; Pedagogy; Education -- Study and teaching; Education, Higher; Decolonization; Special education; Hearing disorders; Leadership; HIV (Viruses); AIDS (Disease); Sex instruction; Counseling